2017
DOI: 10.1186/s13041-016-0283-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute stress enhances the glutamatergic transmission onto basoamygdala neurons embedded in distinct microcircuits

Abstract: Amygdala activation is known to be critical for the processing of stressful events in brain. Recent studies have shown that the projection neurons (PNs) in amygdala, although architecturally intermingled, are integrated into distinct microcircuits and thus play divergent roles in amygdala-related behaviors. It remains unknown how stress regulates the individual amygdala PNs embedded in distinct microcircuits. Here, by using retrograde tracing and electrophysiological recording in in vitro slices, we explored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Similar to earlier findings that acute stress exposure caused immediate but temporary activation of amygdala neurons (32), we observed that the c-fos expression in BLA PNs and their intrinsic excitability and firing to dmPFC inputs returned to baseline 1 day after ARS. BLA→dmPFC PNs and BLA↛dmPFC PNs showed equivalent habituation to ARS, extending our recent finding that ARS similarly and temporarily augmented glutamatergic transmission onto these two PN populations (33). Thus, there appears to be minimal divergence in how these populations respond to an intense but short-lasting stressor.…”
Section: Discussionsupporting
confidence: 82%
“…Similar to earlier findings that acute stress exposure caused immediate but temporary activation of amygdala neurons (32), we observed that the c-fos expression in BLA PNs and their intrinsic excitability and firing to dmPFC inputs returned to baseline 1 day after ARS. BLA→dmPFC PNs and BLA↛dmPFC PNs showed equivalent habituation to ARS, extending our recent finding that ARS similarly and temporarily augmented glutamatergic transmission onto these two PN populations (33). Thus, there appears to be minimal divergence in how these populations respond to an intense but short-lasting stressor.…”
Section: Discussionsupporting
confidence: 82%
“…We next determined if repeated LMX affected neurophysiological adaptations induced by chronic CORT treatment. We focused on examination of amygdala glutamatergic signaling given the well-established role of enhanced amygdala glutamatergic transmission in anxiety and stress responsivity (Song et al, 2017; Masneuf et al, 2014). Both positive and negative valence stimuli activate BLA cells, and distinct BLA output neurons drive opposing behavioral responses to positive and negative valence stimuli (Gore et al, 2015; Stuber et al, 2011; Kim et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence shows that neuronal intrinsic excitability plays an important role in information processing and storage in the brain ( 20 ). A previous study reported the effect of stress on neural intrinsic excitability in the amygdala, which is involved in governing stress responsivity ( 21 , 22 ). The prefrontal cortex (PFC) integrates information from many cortical and subcortical structures, including the ventral hippocampus, amygdala, and mediodorsal thalamus.…”
Section: Introductionmentioning
confidence: 99%